Distribution of Methicillin Resistant Staphylococcus aureus in Iraqi patients and Healthcare Workers - Al-Dahbi, Ali; Al-Mathkhury, Harith (Iraqi Journal of Science, 2024)
One hundred and six S. aureus were isolated from 250 Nasal swabs ofHealthcare workers and patients at Al- Kadhamia teaching Hospital and Al-Numan hospital, Baghdad, Iraq. The study was undertaken over a period often months between August 2011 and June 2012. S. aureus isolates werediagnosed based on phenotypic traits and biochemical tests. Antibioticssensitivity to 11 antibiotics, revealed that S.aureus is totally resistant toPencillin G (100%), highly resistant to Cefoxitin (alternative to Methicillin)(94.3%) While there are varied resistance percentage for the rest ofantibiotics: Erythromycin (37.7%), Tetracycline (34.9%), Gentamicin(29.3%), Trimethoprim/sulfamethoxazole (50%), Ciprofloxacin (29.2%),and showed highly sensitive to Rifampin (96.2%), Clarithromycin (78.3%)and Clindamycin (73.6%),Whereas Vancomycin intermediate S. aureus(VISA) was 32.1% and 3.8% was Vancomycin resistant S. aureus (VRSA).The incidence of MRSA among S. aureus was 94.3%. It is concluded that S.aureus nasal carriage is a common health problem all over the world andMethicillin resistant S. aureus is an emerging subject even in ourcommunity, which requires further attention and support.